EFEKTIFITAS TEKNIK PERNAPASAN BUTEYKO UNTUK MENINGKATKAN PENGONTROLAN ASMA BRONKIAL DI PUSKESMAS KOTA PADANG - Angraini, Siska Sakti (E-Jurnal Medika Udayana; Vol 13 No 2 (2024): E-Jurnal Medika Udayana, 2024)
ABSTRACT Bronchial asthma is one of the chronic respiratory diseases caused by the narrowing of the airways due to hypersensitivity reactions in the bronchi, resulting in symptoms such as wheezing, coughing, and shortness of breath. When asthma patients experience breathlessness, there is an increase in respiratory frequency and a decrease in oxygen saturation. If not promptly treated, it can lead to oxygen deficiency (hypoxia), which can ultimately result in death. The management of bronchial asthma is typically done with pharmacological therapy aimed at achieving a normal lifestyle, avoiding attacks, and restoring optimal lung function. However, it has not shown significant improvement in preventing bronchial asthma. Non-pharmacological treatment methods, such as Buteyko breathing technique, are expected to complement pharmacological treatment in reducing the frequency of asthma attacks (exacerbations). The Buteyko breathing technique has shown an increase in peak expiratory flow rate (PEFR) values and a decrease in bronchial asthma score values. The objective of this study is to analyze the effectiveness of the Buteyko breathing technique in controlling bronchial asthma in the Padang Health Center area. Before the intervention, the average bronchial asthma control was 15.44, with a standard deviation of 2.279, and a minimum control of 11 and a maximum of 19. After the intervention, the average control increased to 21.69, with a standard deviation of 2.387, and a minimum control of 16 and a maximum of 25. Similarly, bronchial asthma control in the control group showed an increase from 16.19 to 15.38 after the intervention. Statistical tests using independent t-tests showed a significant influence of the Buteyko breathing technique on bronchial asthma control, with a p-value of 0.000 (p?0.05). This indicates that the Buteyko breathing technique has a significant impact on improving bronchial asthma control. Therefore, this research provides evidence that the Buteyko breathing technique can be a valuable addition to the treatment of bronchial asthma, helping patients achieve better control of their condition and reducing the risk of asthma attacks. Keywords: Buteyko breathing technique; Breathing patterns.